L27 Supporting Function Through Engagement With Meaningful Occupation. (17th September 2014) - McCaffrey, S; Hoblyn, J
Abstract : Background: Huntington's disease (HD) is a hereditary neurological disorder that leads to progressive degeneration of the physical, cognitive and emotional self. A clear multidisciplinary approach is essential in maintaining quality of life for those affected by HD. Occupational Therapy (OT) has a key role to play in maximising function and quality of life for those with HD. Internationally there is a dearth of research and best practice guidelines relating to OT and HD. Research available primarily focuses on Personal Acts of Daily Living (PADLs) and community settings, not involving those in long term care. Method/intervention: It was observed in practice that a number of clients on our service with HD experienced considerable difficulties initiating engagement with meaningful occupation. The Model of Human Screening Tool (MUST) was selected as the assessment tool alongside a collateral history. Clients were assigned to group programmes or 1:1 intervention as indicated. A unique 'Supporting me to Engage' document was then developed outlining individualised approaches for each client to enable consistency of approach from all staff. Outcome: Enabling clients with HD to engage with meaningful occupation can improve overall occupational functioning, quality of life and reduce instances of behaviours that may prove challenging. Improvements in motivation for occupation, pattern of occupation, communication and interaction were observed. Due to the degenerative nature of HD, programmes must remain responsive to any deterioration in function. Conclusions: Further research is required in this area in order to validate and support the development of OT Assessments specifically for those with HD.